New reports of Bursaphelenchus species associated with conifer trees in Romania. Issue 3 (16th December 2014) - Calin, M.; Costache, C.; Braasch, H.; Zaulet, M.; Buburuzan, L.; Petrovan, V.; Dumitru, M.; Mota, M.; Vieira, P.; Belbahri, L.
Summary The 2013 annual monitoring programme for the pinewood nematode, Bursaphelenchus xylophilus, analysed a total of 267 wood samples collected from declining or symptomatic coniferous trees distributed among national forests, gardens, public parks, distribution centres, wood‐processing industries, as well as 104 samples collected from wood packing material originated from several other countries. From a total of eight species found, five have been previously reported from Romania, while three other species (Bursaphelenchus abietinus, Bursaphelenchus fraudulentus and Bursaphelenchus fuchsi) represent new findings for Romania. In addition, B. mucronatus was found in packing wood originated from Russia. Herein, we provide a morphological, morphometric and molecular characterization for the new species found for Romania. Bursaphelenchus xylophilus was not detected.